Implementing a Dashboard for Monitoring Sales Transaction Data - Olva, Maria; Dwiputri Permatasari, Ririt; Majid, Sanusi; Syair, Pratiwi; Suganda, Afdal (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Penelitian ini bertujuan untuk mengimplementasikan dasbor pada pemantauan data transaksi penjualan di PT. Prima Labeling. Data pada sistem diperoleh dari hasil aliran informasi pengolahan data penjualan dan aliran data informasi pemanfaatan dasbor pada pemantauan data transaksi transaksi penjualan pada PT. Prima Labeling. Model sistem yang digunakan adalah UML yang mana pengembangan sistem penelitian menggunakan metode OOAD. Sistem informasi dirancang berbasis situs web dengan menggunakan bahasa pemrograman PHP dan database MySQL. Teknik penelitian kualitatif, dengan mengumpulkan data-data dan informasi secara deskriptif. Hasil penelitian ini pengguna dapat mengelola transaksi dengan mudah sekaligus dapat melakukan memantau transaksi penjualan pada waktu yang sebenarnya sehingga mempermudah proses pengelolaan data dan transaksi penjualan pada PT. Prima Labeling. Implementing a Dashboard for Monitoring Sales Transaction Data Abstract: Objective of the research is to monitoring sales transaction data at PT. Prima Labeling by implemented a dashboard. Data on the system is obtained from the results of the sales data processing information flow and dashboard utilization information of data flow monitoring sales transaction data at PT. Prima Labeling. System model used is UML where the research system development uses the OOAD method. Information system is designed based on a website using the PHP programming language and MySQL database. Qualitative research techniques is applied by collecting data and information descriptively. Results of this research users can easily manage transactions as well as monitor sales transactions in real time, thus simplifying the process of data management and sales transactions at PT. Prima Labeling. Keywords: Dashboard, Monitoring, OOAD, Sales Transactions, UML.